(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the unique challenges involved in translating economic terms from English into Uzbek. It discusses the linguistic and cultural contexts, identifies specific challenges such as terminological gaps and polysemy, and suggests effective strategies for translation. The study includes case studies on translating "Gross Domestic Product" and "Quantitative Easing," offering practical insights for translators. The article aims to enhance understanding and improve practices in economic term translation between English and Uzbek.